A bibliography on Tirukkuṟaḷ - Rajagopalan, R. (Institute of Asian Studies, 2001)
On an ancient Tamil didactic verse work, by Tiruvaḷḷuvar, Tamil poet
Includes indexes
Keywords: Tirukkur̲aḷ; Tiruvaḷḷuvar; Bibliografie